Managing risk in projects - Hillson, David, 1955- (Farnham, England : Burlington, VT : Gower, 2009)
The book makes a good representation of project, program and portfolio management and how risk management needs to be undertaken at each level.
Uncertainty and risk -- Risk and projects -- Managing risk in practice -- Risk and people -- Integrating risk management with wider project management -- The bigger picture -- Making risk management work.
Includes bibliographical references (p. [97]-99) and index.
rua 29/11/13
Loans
Keywords: Risk management; Project management; Project Management (PM); Project Risk Management [Knowledge Area]